OPTIMIZATION OF ADHESIVE FIXATION IN DIRECT COMPOSITE RESTORATIONS: THE ROLE OF DELAYED POLYMERIZATION - Baido, O.S.; Marchenko, A.V. (World of Medicine and Biology, 2025)
The purpose of this review was to analyze the literature regarding the influence of polymerization time, specifically comparing immediate and delayed polymerization techniques, on the quality and longevity of adhesive bonding in direct composite restorations. Based on an analysis of recent scientific publications (from the last 5 years indexed in Scopus/Web of Science), key aspects of dentin adhesion mechanisms, polymerization kinetics, shrinkage stress development, and factors influencing bond strength were examined. While the benefits of Immediate Dentin Sealing for indirect restorations are well-documented, the application of delayed polymerization principles to direct restorations remains less explored, with contradictory results in existing preclinical studies regarding optimal delay times and clinical significance. Studies suggest potential advantages of delayed polymerization (e.g., 5 minutes) in improving bond strength and marginal adaptation, possibly due to more complete initial polymerization conversion and stress relaxation within the adhesive layer before composite placement. However, a lack of standardized protocols and long-term clinical data persists. Further research, particularly well-designed clinical trials, is needed to establish evidence-based protocols for potentially optimizing direct composite restorations through controlled polymerization timing.
Keywords: dentin bonding; delayed polymerization; immediate dentin sealing; bond strength